Kepemimpinan Kepala Desa dalam Mengembangkan Nilai-Nilai Islami kepada Masyarakat Desa Banjarsari - Achmad Choliqus Muzzaqy; Mardiyah (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2018)
Islamic values: honesty, fairness, responsibility, trustworthiness, hard work, istiqamah and sincerity are universal values ​​that are very necessary to use as a guide in carrying out this life. Its use is not only devoted to Muslims, but also non-Muslim religious people need to apply Islamic values ​​in this life. The aim is to create self-prosperity and the environment, good prosperity in the world for Muslims and non-Muslims as well as prosperous endings for Muslims. The discussion to be discussed in this study are: (a) What is the leadership of the Village Head in developing Islamic values ​​to the Banjarsari village community?, (b) How are Islamic values ​​developed by the Village Head to the Banjarsari village community?, (c) What are the supporting and inhibiting factors of the Village Head in developing Islamic values ​​to the Banjarsari village community?. This type of research is qualitative with a case study research approach. The data collection techniques are using interviews, observation and documentation. While the data analysis technique uses descriptive analysis. Furthermore, checking the validity of the data is done by extending observations, increasing perseverance in research and triangulation of case analysis. The results of the study show that: (a) the leadership of the Village Head in developing Islamic values ​​to the Banjarsari village community, namely through the implementation of their duties and obligations as Village Heads, among others, fostering village communities in collaboration with village officials and community leaders. (b) Islamic values ​​developed by the Village Head to the Banjarsari village community have several forms, including: honesty, fairness, responsibility, trustworthiness, hard work, piety, and sincerity. (c) Supporting and inhibiting factors of the Village Head in developing Islamic values ​​to the Banjarsari village community, among others, there are factors such as: internal encouragement, scientific and qualified experience, financially capable, truly holding on to Islamic law, the community religious, and people who need problem solving, and for inhibiting factors include: differences in the depth of knowledge of the device, some people who contradict the Village Head, and people who consume drugs and the like